Keterampilan Berbicara Bahasa Jerman Melalui Media Zoom - Irawati Azis; Syukur Saud; Abdul Kasim Achmad (Phonologie : Journal of Language and Literature, 2022)
Abstract. This study aims to know the planning, process, and results of the German speaking skills of class XI IPA 1 SMAN 8 Gowa students through Zoom media. This research was a class action research consists of two cycles. The data of this research consists of two data types: qualitative and quantitative data. Qualitative data were obtained through teacher and student observations and quantitative data from the German speaking skill test. The data were analyzed using the percentage technique. The results showed that speaking skills with an average score obtained by students in the first cycle reached 54% and the second cycle reached 82%. These results indicate that the Zoom media can improve the German speaking skills of class XI IPA 1 SMAN 8 Gowa students.Keyword: Speaking Skills, Zoom, German